Rheological Properties of Fish and Mammalian Gelatin Hydrogels as Bases for Potential Practical Formulations - Svetlana R. Derkach; Nikolay G. Voron’ko; Yulia A. Kuchina; Daria S. Kolotova; Vladimir A. Grokhovsky; Alena A. Nikiforova; Igor A. Sedov; Dzhigangir A. Faizullin; Yuriy F. Zuev (Gels, 2024)
Hydrogels have the ability to retain large amounts of water within their three-dimensional polymer matrices. These attractive materials are used in medicine and the food industry; they can serve as the basis for structured food products, additives, and various ingredients. Gelatin is one of widely used biopolymers to create hydrogels that exhibit biocompatibility and tunable rheological properties. In this study, we offer a comparative analysis of rheological properties of gelatin-based hydrogels (C = 6.67%), including mammalian gelatins from bovine and porcine skins and fish gelatins from commercial samples and samples extracted from Atlantic cod skin. Mammalian gelatins provide high strength and elasticity to hydrogels. Their melting point lies in the range from 22 to 34 °C. Fish gelatin from cod skin also provides a high strength to hydrogels. Commercial fish gelatin forms weak gels exhibiting low viscoelastic properties and strength, as well as low thermal stability with a melting point of 7 °C. Gelatins were characterized basing on the analysis of amino acid composition, molecular weight distribution, and biopolymer secondary structure in gels. Our research provides a unique rheological comparison of mammalian and fish gelatin hydrogels as a tool for the re-evaluation of fish skin gelatin produced through circular processes.